Implementing Multisensory Pedagogy to Strengthen Teachers' Role in Addressing Early Reading Challenges - Susanti, Rini Dwi; Dewi, Annisya Aulia; Zulaikhah, Siti (LP. Ma'arif Janggan Magetan, 2025)
The objectives in the implementation of multisensory techniques to overcome the difficulties of early reading for first graders are also to determine supporting and inhibiting factors of learning, with outcomes described by employing a qualitative descriptive method at SD NU Tanwirul Qulub Kudus. The data were collected through observation, interview, and documentation. Triangulation was used to test the validity of the data and was analyzed through reduction, presentation, and drawing a conclusion. The results showed that a multisensory approach-phonics cards, writing exercises, interactive feedback, and special assistance to the students diagnosed with dyslexia-has satisfactorily improved the learners' abilities in early reading.Average ability increased from 58% before implementation to 84% after using the multisensory strategy. Factors supporting the success of the implementation were interesting media, gradual delivery of materials, active teacher-student interaction, and timely feedback on students' work. The inhibiting factors were the limited time and students' varying abilities. Results imply that the practical and effective model multisensory innovative approach to developing emergent literacy, can be used as a real Indonesian language program in elementary schools.